Global Health Security Preparedness And Response Strategies - A Systematic Review (The Review of Diabetic Studies, 2025)
Background: The growing frequency of infectious disease outbreaks, pandemics, and transnational health threats has emphasized the importance of global health security. Effective preparedness and response strategies are essential to reduce morbidity, mortality, and socioeconomic disruption during public health emergencies. Despite international frameworks and commitments, significant variation exists in health security capacities across countries. Objective: This systematic review aims to assess global health security preparedness and response strategies, identify key components associated with effective emergency management, and highlight gaps that hinder optimal global health emergency readiness. Methods: A systematic search was conducted across major electronic databases, including PubMed, Scopus, Web of Science, and Embase, as well as relevant gray literature. Studies evaluating preparedness frameworks, response strategies, or health system capacities related to public health emergencies were included. Study selection, data extraction, and quality assessment were performed independently by reviewers, and findings were synthesized using a narrative thematic approach. Results: The review identified critical preparedness elements such as disease surveillance systems, laboratory capacity, health workforce training, risk communication, and multisectoral coordination. Effective response strategies included rapid case detection, contact tracing, emergency logistics, and integrated governance mechanisms. Countries with established legal frameworks, regular simulation exercises, and sustained funding demonstrated more timely and coordinated responses. Persistent challenges included workforce shortages, inequitable resource distribution, limited cross-border data sharing, and weak health system resilience in low-resource settings. Conclusions: Global health security preparedness and response depend on integrated, well-resourced, and continuously evaluated systems. Addressing existing disparities through sustained investment, international cooperation, and standardized preparedness metrics is essential to strengthen global resilience against future public health emergencies.